Polarimetric Detection, Characterization and Remote Sensing - Mishchenko, Michael I.; Yatskiv, Yaroslav S.; Rosenbush, Vera K.; Videen, Gorden; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
As the need for accurate and non-invasive optical characterization and diagnostic techniques is rapidly increasing, it is imperative to find improved ways of extracting the additional information contained within the measured parameters of the scattered light. This is the first specialized monograph on photopolarimetry, a rapidly developing, multidisciplinary topic with numerous military, ecological remote-sensing, astrophysical, biomedical, and technological applications. The main objective is to describe and discuss techniques developed in various disciplines to acquire useful information from the polarization signal of scattered electromagnetic waves. It focuses on the state-of-the-art in polarimetric detection, characterization, and remote sensing, including military and environmental monitoring as well as terrestrial, atmospheric, and biomedical characterization. The book identifies polarimetric techniques that have been especially successful for various applications as well as the future needs of the various research communities. The monograph is intended to facilitate cross-pollination of ideas and thereby improve research efficiency and help advance the field of polarimetry into the future. The book is thoroughly interdisciplinary and contains only invited review chapters written by leading experts in the respective fields. It will be useful to science professionals, engineers, and graduate students working in a broad range of disciplines: optics, electromagnetics, atmospheric radiation and remote sensing, radar meteorology, oceanography, climate research, astrophysics, optical engineering and technology, particle characterization, and biomedical optics.
Stellar Spectropolarimetry: Basic Principles Observing Strategies, and Diagnostics of Magnetic Fields -- Reflection Symmetry of a Sphere$1 (Bs Internal Field and its Consequences on Scattering: Behavior of the Stokes Parameters -- Light Scattering by Large Faceted Particles -- Regularization of Inverse Problems in Atmospheric Remote Sensing -- Light Scattering Resonances in Small Particles with Electric and Magnetic Optical Properties -- Laboratory Measurements of Light Scattered by Clouds and Layers of Solid Particles Using an Imaging Technique -- High Sensitivity Polarimetry: Techniques and Applications -- Aerosol Retrievals under Partly Cloudy Conditions: Challenges and Perspectives -- Astrophysical Polarimetry in Ukraine -- Photopolarimetric Remote Sensing of Aggregates in Cosmic Dust -- Astrobiological Remote Sensing with Circular Polarization -- Inferring Properties of Dust Within Small Bodies of the Solar System through Observations and Simulations of the Linear Polarization of Scattered Solar Light -- Semi-Empirical BRDF and BPDF Models Applied to the Problem of Aerosol Retrievals over Land: Testing on Airborne Data and Implications for Modeling of Top-of-Atmosphere Measurements -- An Estimation of Surface Albedo from the SEVIRI/MSG Observing System by Using POLDER BRDF Measurements -- Plasmonic Spectroscopy of 2D Densely Packed and Layered Metallic Nanostructures -- Opposition Optical Phenomena in Planetary Astrophysics: Observational Results -- Mueller-Matrix Characterization of Biological Tissues -- Plasmonic Optical Properties and the Polarization Modulation Technique -- Inferring Microstructure and Turbulence Properties in Rain through Observations and Simulations of Signal Spectra Measured with Doppler-Polarimetric Radars.s
Keywords: Geography; Meteorology; Remote sensing; Earth Sciences; Remote Sensing/Photogrammetry.; Environmental Monitoring/Analysis.; Optics, Optoelectronics, Plasmonics and Optical Devices; Astrophysics and Astroparticles; Meteorology/Climatology.